Analisis Efektivitas Penggunaan Metode Kontrasepsi Jangka Panjang (MKJP) dalam Pencegahan Stunting di Wilayah Kerja Puskesmas Kecamatan Bintuhan, Kabupaten Kaur - Aprianty, Henny; Aski, Hendri; Sakti, Budiman; Purnawan, Heru (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka, 2025)
Analysis of the Effectiveness of Using Long-Term Contraceptive Methods (MKJP) in Preventing Stunting in the Working Area of Bintuhan Health Center. This study aims to analyze the effectiveness of Long-Term Contraceptive Methods (MKJP) in preventing stunting and identify the barriers to their implementation in the working area of Puskesmas Bintuhan. A qualitative approach was used, with data collected through in-depth interviews, observations, and document analysis. Informants included the Head of DP3APPKB Kaur Regency, the Head of UPTD Puskesmas Bintuhan, health workers, posyandu cadres, community leaders, and reproductive-age couples. The results show that the MKJP program effectively prevents stunting by targeting reproductive-age couples, particularly those aged 20–50 years, focusing on birth spacing. Socialization efforts, including counseling, field visits, and media campaigns, have improved public awareness. However, program acceptance remains hindered by social stigma, fear of side effects, and limited access to services in remote areas. Barriers to program implementation include myths surrounding MKJP, cultural norms placing contraceptive responsibility on women, limited male involvement in decision-making, and inaccurate information. These factors significantly influence the community’s acceptance of MKJP, especially in rural areas. In conclusion the MKJP program plays a crucial role in preventing stunting, but its success requires more inclusive educational strategies, culturally sensitive approaches, cross-sector collaboration, and improved access to healthcare services in remote areas. This program is expected to support reproductive health and family welfare sustainably and become reference in the future.